A study on multi-project management in the mining and geology sector in Serbia: A case analysis - Stanković T.; Radojević T.; Jovanović I. (Journal of Mining and Metallurgy. Section A: Mining)
This paper describes the basic concept of multi-project management in the science and research organizations in Serbia and worldwide. A brief discussion was held on the sources of funding for these projects, and several proposed solutions to problems that may arise in the management of projects in the field of mining, were considered from the perspective of worldwide practice. An overview of completed projects in the field of mining and geology in the period from 2010 to 2023 is given using the example of a case study of a selected scientific and research organization, the Bor Mining and Metallurgy Institute, by type and number of projects and sources of funding. A brief analysis of the success of multi-project management in this institution was carried out. Considering the years of project development, it was determined it was found that the greatest success of multi-project management has been achieved in the last five years, which indicates the good business strategy of the Institute. The financing structure has shown that the largest number of projects in this institution, in the given period was financed by the private sector, i.e. the Chinese mining company Serbia Zijin Copper Bor (formerly RTB Bor).